2017
DOI: 10.1039/c6ay02674e
|View full text |Cite
|
Sign up to set email alerts
|

First detection of seven phthalate esters (PAEs) as plastic tracers in superficial neustonic/planktonic samples and cetacean blubber

Abstract: Ingestion of plastics and microplastics by marine organisms may have physical and toxicological noxious effects creating a serious threat to marine species. There is a need to develop methods to evaluate the plastic exposure in free-ranging marine wildlife particularly related to microplastic ingestion. To this aim, seven phthalate esters (PAEs) were analysed, as plastic tracers, in neustonic/planktonic samples and skin biopsy samples of four cetacean species from the North-Western Mediterranean Sea. Among all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
47
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 123 publications
(52 citation statements)
references
References 54 publications
4
47
1
Order By: Relevance
“…In addition, seven phthalate esters (plastic additives) were detected in microplastic/neustonic samples and in skin biopsies of several cetacean species collected in the same protected areas (Baini et al, 2017), confirming the occurrence of associated plastic chemicals and their related risk to the inhabiting fauna.…”
Section: Discussionmentioning
confidence: 83%
“…In addition, seven phthalate esters (plastic additives) were detected in microplastic/neustonic samples and in skin biopsies of several cetacean species collected in the same protected areas (Baini et al, 2017), confirming the occurrence of associated plastic chemicals and their related risk to the inhabiting fauna.…”
Section: Discussionmentioning
confidence: 83%
“…Similarly, phthalate concentrations in birds have been correlated with numbers of pieces of plastic ingested by birds (Hardesty et al, 2015). In another study, a significant correlation has been demonstrated among different phthalate esters present in samples taken in the same area of microplastics, plankton and bubbler samples of different cetacean species (Baini et al, 2017).…”
Section: Opfrs Vs Pbdesmentioning
confidence: 85%
“…It is not particularly surprising to find MEP and MEHP in dolphins, since both of these compounds have been detected in other aquatic wildlife, such as blue mussel tissue ( Mytilus edulis , Blair et al, ), muscle of Dungeness crab ( Metacarcinus magister , Blair et al, ), and muscle, brain, liver, and bile from multiple species of fish (Fourgous et al, ; Ros et al, , ; Valton et al, ). MEHP has been detected in blubber of fin whales ( Balaenoptera physalus , Fossi et al, , ), muscle of basking sharks ( Cetorhinus maximus , Fossi et al, ), blubber and skin from a bottlenose dolphin (Baini et al, ), blubber and skin from a Risso's dolphin ( Grampus griseus , Baini et al, ), blubber and skin from striped dolphins ( Stenella coeruleoalba , Baini et al, ), and urine from American alligators ( Alligator mississippiensis , Brock et al, ). Sarasota Bay dolphins revealed individual variability in the type and amount of phthalate exposure.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies of phthalate metabolites in the blubber of marine mammals inhabiting different regions of the Mediterranean Sea have provided evidence that phthalate metabolites, specifically MEHP, may be indicative of environmental microplastic contamination (Baini et al, ; Fossi et al, , ). If true, this suggests that Sarasota Bay and surrounding areas could be polluted with plastic due to contaminated runoff or effluents; however, to our knowledge, systematic studies of microplastic contamination have not been reported for Sarasota Bay.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation